“Writing Javanese Script” Application as a Support for Learning to Write Javanese Script in Junior High Schools - Kholifaturrohmah, Nur; Insani, Nur Hanifah (LPPM Undiksha, 2025)
The ability of Grade VIII students at SMP to write in Javanese script remains relatively low, indicating the need for more effective learning media to improve student learning outcomes. This study aims to determine the effectiveness of the